2014
DOI: 10.1049/el.2014.1692
|View full text |Cite
|
Sign up to set email alerts
|

Normally‐off vertical‐type mesa‐gate GaN MOSFET

Abstract: A vertical-type mesa-gate GaN metal-oxide semiconductor field-effect transistor (MOSFET) has been fabricated. The mesa-gate structure can be easily achieved by a single deep etch to the n + -GaN which is the drain of the device, whereas the trench-gate structure, the commonly used structure for the vertical-type MOSFETs, requires an additional etching process to define the gate region. The mesa-gate GaN MOSFET exhibited a normally-off operation with the threshold voltage of 3 V, a normalised drain current of ∼… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Under the OFFstate condition, the gate bias of −25 V produced a large electric field (∼4 MV cm −1 ) on the Al 2 O 3 gate dielectric. This large electric field plays a vital role on high leakage current densities and breakdown of the oxide layer [26][27][28]. In addition, the n − -GaN drift layer in the device structure also acts as a high voltage sustaining layer and by increasing its thickness, the breakdown voltage could be improved [29].…”
Section: Resultsmentioning
confidence: 99%
“…Under the OFFstate condition, the gate bias of −25 V produced a large electric field (∼4 MV cm −1 ) on the Al 2 O 3 gate dielectric. This large electric field plays a vital role on high leakage current densities and breakdown of the oxide layer [26][27][28]. In addition, the n − -GaN drift layer in the device structure also acts as a high voltage sustaining layer and by increasing its thickness, the breakdown voltage could be improved [29].…”
Section: Resultsmentioning
confidence: 99%
“…Several approaches have been reported to modulate the 2DEG channel and realize normally-off operation, such as recessed-gate structure [1], hybrid MIS gate [2], fluoride-based plasma-treatment [3], thin-barrier structure [4], p-n junction gate [5], ferroelectric gate [6], and some combined approaches [7][8][9][10][11]. Besides, vertical-type mesa-gate GaN transistors and groovetype channel combining polar and nonpolar AlGaN/GaN heterostructures, utilizing etching and regrowth technologies, were also reported [12][13][14]. Among these approaches, etching process was commonly employed to fabricate recessed gate, vertical-mesa or groove-structure, which could inevitably induce some etching damage and hence degrade the device performance [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the enhancement mode (E-mode) device has advantages in high-speed and low power dissipation compared to the depletion mode (D-mode) devices normally based on the polar nature of III-N materials. [2][3][4][5] Therefore, AlInN/GaN HEMT with the E-mode is worthy of extensive study. It has been shown that the self-heating effect of GaN-based HEMTs has a significant negative impact on device performance [6][7][8] because of the increase in the channel temperature with the increase in the lattice temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The HEMT performance is therefore significantly improved. Moreover, the enhancement mode (E‐mode) device has advantages in high‐speed and low power dissipation compared to the depletion mode (D‐mode) devices normally based on the polar nature of III‐N materials . Therefore, AlInN/GaN HEMT with the E‐mode is worthy of extensive study.…”
Section: Introductionmentioning
confidence: 99%